Highly sensitised patients awaiting deceased donor renal transplants are disadvantaged by the presence of denatured HLA antibody detected in routine HLA antibody testing. (22nd February 2022) - Battle, Richard K.; Rennie, Trijntje J. W.; Phelan, Paul J.; Abel, Angela A.; McConnell, Sylvia; Turner, David M.
Abstract : Luminex single antigen bead (SAB) assays used to detect HLA antibodies may artificially increase sensitisation in highly sensitised patients (HSP). The presence of denatured HLA (dHLA) within the assay enables antibodies specific to cryptic HLA epitopes to bind, such antibodies are not clinically relevant. We sought to exclude dHLA reactivity in a cohort of very HSP, calculated reaction frequency (cRF) 95%–100% and determine the effect upon sensitisation. Such patients have limited access to suitable donors and small changes in their HLA antibody profile, particularly where their cRF is 100%, can increase their opportunity of a transplant. We determined the presence of dHLA by aligning antibody reactivity which did not correspond to known HLA class I epitope mismatches with the results of assays modified to detect class I dHLA. 130 class I dHLA reactions were identified within 11 HSP, all of whom had clear sensitising events. cRF was corrected for dHLA, mean cRF 98.2% (93–100) pre and 95.5% (87–100) post correction ( p = 0.0156). An increase in the number of predicted compatible donors ( p = 0.0078) after dHLA correction was demonstrated. Two manufacturers SAB assays were used. A reduction of patients with 100% cRF was observed for both manufactures. dHLA is contributing to sensitisation in HSP and is detrimental to their chances of receiving a compatible transplant. The observed dHLA reactivity varied according to kit manufacturers ( p = 0.0001), this is potentially a useful finding for laboratories wishing to discriminate between nHLA and dHLA, but without the resources required to regularly perform dHLA assay and epitope analyses.